Experiences in the integration of children and young people of Polish descent in Germany. Empirical contributions - Kalkowska, Magda (Kultura-Społeczeństwo-Edukacja, 2019)
The accommodation of children and young people of foreign descent to new life conditions and educational challenges abroad is a process that takes place primarily in the context of social interactions. The aim of the article below is to present selected experiences in terms of integrating schoolchildren of Polish origin in Germany. The author considers the presentation of school space as an integration microcosm of its own to be of particular importance. It is worth noting that the German educational system in the present form often discriminates againsts choolchildren of foreign descent and limits the opportunities for further education. The author’s own empirical verifications served as the research illustration in the text. The verifications, though carried out on a small sample, indicate some timeless trends among young Polish immigrants.